THE SEVENTH GRADE STUDENTS OF SMPN 1 ERIS MASTER THE LANGUAGE SKILLS, ESPECIALLY THE ABILITY OF READING COMPREHENSION AND THEIR COMPONENTS, ESPECIALLY THE MASTERY OF VOCABULARY - Tampi, Gloria; Tuerah, Ignatius Javier; Olii, Sanerita T. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
This project is about the correlation between the vocabulary mastery and reading comprehension among the seventh grade students of SMP N 1 Eris. The objectives of the study were: to find out the students’ vocabulary mastery and reading comprehension of the seventh grade students of SMP N 1 Eris in the academic year 2019/2020, and to find out whether or not there is a significant correlation between the students’ vocabulary mastery and their reading comprehension. The writer applied cluster random sampling to determine the sample. The total sample of this research followed by 80 students. The technique of collecting data was by using a test. A try out test was also done to find out the validity. After the data of the students’ vocabulary mastery and their achievement in reading comprehension were collected, the data were statistically computed to find out the correlation between the two variables. From the tests, it was found out that the mean of the scores of the vocabulary test is 58. 06. It means that the mean of the scores of the vocabulary test is fair. The mean of the scores of the students’ achievement in reading comprehension is 61. 62, which means that the mean of the scores of reading comprehension test is fair. The result of applying the rxy distribution is shows that the coefficient correlation is 0. 417. It means that there is a significant correlation between the vocabulary mastery and reading comprehension. It is suggested that to have a good mastery of reading comprehension, students should have a good mastery of vocabulary.